Two-Year Follow-Up: Therapeutic Success with Respect to Axial Length of Stand-Alone Xen45 Gel Stent Implantation and Combined Procedures - Gernhart, Markus; Hohberger, Bettina; Laemmer, Robert (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Up to now, no data have been available on the therapeutic success rate of Xen45 gel stent with respect to axial length (AL). The present study aimed to investigate a potential influence of AL on therapeutic success in stand-alone Xen45 gel stent implantation or combination with cataract surgery in open-angle glaucoma patients (OAG) with a follow-up of 2 years.Materials and Methods In this retrospective observational study, 98 eyes of 87 glaucoma patients of the Department of Ophthalmology, University of Erlangen Nürnberg, and from the Erlangen Glaucoma Registry (NCT00494923; ISSN 2191-5008, CS-2011) underwent stand-alone Xen45 gel stent implantation or a combination with cataract surgery. Therapeutic success was defined as ≥ 20% IOP reduction with the same or fewer anti-glaucomatous eye drops needed compared to baseline, yet without additional glaucoma-related surgery (expect bleb needling). Therapeutic failure was classified as any additional glaucoma-related surgery, IOP reduction < 20% or if more local anti-glaucomatous eye drops were applied compared to baseline.Results The therapeutic success rate was 60.7% (1 year) and 62.5% (2 years). No statistical difference was observed when procedures were combined with cataract surgery (p > 0.05). Subgroup analysis yielded no significantly different therapeutic success when considering glaucoma subtype [1 year: 61.5% (POAG), 60% (SAOG), 2 years: 54.5% (POAG), 69.2% (SOAG); p > 0.05]. Anti-glaucomatous medication use was lowered from 2.72 ± 1.04 at baseline to 0.61 ± 0.99 (1 year) and 0.7 ± 1.04 (2 years). The therapeutic success rate was seen to be independent of axial length for group and subgroup analysis (p > 0.05). Emmetropic eyes (22.0 – 24.5 mm) showed a statistically higher needling rate than myopic eyes (> 24.5 mm, p = 0.02).Conclusion Minimal invasive glaucoma surgery is one therapeutic option in OAG eyes, with good reduction in IOP even after 24 months (with additional bleb needling). Therapeutic success seemed to be independent of axial length in the present study.
Keywords: glaucoma; open-angle glaucoma; Xen Stent; axial length; myopia